2019
DOI: 10.1515/eces-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis: Trickling Filter/Activated Sludge or Nitrifying Trickling Filter/Activated Sludge?

Abstract: The performance and economic simulation and modeling are crucial for accurate and rapid designing, construction, and forecasting future economic needs of municipal wastewater treatment plants (MWWTPs). In this study, combined nitrifying trickling filter/activated sludge (NTF/AS) process was suggested for the modernization of a MWWTP and the performance and economics of MWWTPs based on the combined TF/AS process and combined NTF/AS process were analyzed and compared. In real, the performance, total project cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Owing to the high SO2 removal efficiencies from 50% up to 98%; probable reusable of reaction products; relatively simple retrofitting; and relatively lower price and availability of reagents; until now most widely used technology in the removal of sulfur from flue gas is flue gas desulfurization (FGD) technology in which sulfur gases react with alkali chemical material and goes out from the gas phase. In once‐through FGD technologies, the spent sorbent is disposed of as a waste or utilized as a byproduct while in regenerable FGD technologies, absorbed or reacted sulfur compounds is released from the sorbent during the sorbent's regeneration, and the SO2 may be further processed to yield sulfuric acid, elemental sulfur, or liquid sulfur dioxide .…”
Section: Thermal Decomposition (Roasting) Processesmentioning
confidence: 99%
“…Owing to the high SO2 removal efficiencies from 50% up to 98%; probable reusable of reaction products; relatively simple retrofitting; and relatively lower price and availability of reagents; until now most widely used technology in the removal of sulfur from flue gas is flue gas desulfurization (FGD) technology in which sulfur gases react with alkali chemical material and goes out from the gas phase. In once‐through FGD technologies, the spent sorbent is disposed of as a waste or utilized as a byproduct while in regenerable FGD technologies, absorbed or reacted sulfur compounds is released from the sorbent during the sorbent's regeneration, and the SO2 may be further processed to yield sulfuric acid, elemental sulfur, or liquid sulfur dioxide .…”
Section: Thermal Decomposition (Roasting) Processesmentioning
confidence: 99%
“…The emission of NOx and SOx must be inhibited, or the emitted gases have to be converted into harmless products or removed. [12][13][14][15] In addition, the catalytic performance of the zeolites on polymer cracking is degraded through repeated regeneration processes and the coke-deposited zeolites with poor catalytic activity must be finally diverted for another purpose or discarded. Therefore, the development of new methods to utilize the deposited coke on zeolites has been desired.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most common and the most perilous air pollutants are the oxides of sulfur (SO 2 and SO 3 ). 4,5 In 1952, the elevated levels of SO 2 and black smoke caused >1,000 extra deaths within 5 d in London. 1 A study published in 1973 concluded that in New York, the mortality rate was 2% higher than expected for 260 d with SO 2 concentrations of ⩾500 μg m −3 .…”
mentioning
confidence: 99%